Comparison of particulate matter emission and soluble matter collected from combustion cigarettes and heated tobacco products using a setup designed to simulate puffing regimes - Ana Amorós-Pérez (Elsevier, 2021)
An experimental setup was designed and optimized to collect particulate matter suspended in cigarettes smoke or in the aerosol generated during the use of heated tobacco products (HTPs). The setup is mainly based on a gas washing flask containing water where particulate matter and soluble compounds can be trapped, resembling interaction in the body. This system allows to perform puffing experiments in conditions similar to those of the Health Canada Intense puffing regime. In the study, cigarettes and Heets (in IQOS heater) from Philip Morris Products were used. Complementary characterization of this particulate matter has been extracted from experiments on a gas washing flask containing isopropanol. Total organic carbon analysis, laser diffraction, UV-vis spectrophotometry and transmission electron microscopy measurements have shown that cigarette smoke contains a large number and content of compounds soluble in water and isopropanol, together with solid particles generated during combustion. In contrast, negligible presence of non-combustion related particles was detected in Heets aerosol samples. These facts, together with the higher amount of water soluble compounds and higher number of polyaromatic hydrocarbons detected in the cigarettes smoke, allow to conclude that HTPs are less harmful than combusted cigarettes.